A high proportion of new energy access–combined cooling, heating, and power system planning method. (22nd August 2019) - Zhang, Jiahui; Zhang, Shuyu; Niu, Yuguang
Summary: Distributed generation (DG) technologies are environmentally friendly and have low operating costs, and thus, distributed generators are widely used for the energy supplies of buildings. Solar energy used for on‐demand heating of buildings is also a mature technology that is environmentally friendly and inexpensive and has a short recycling life cycle. This paper proposes a high proportion of new energy access–combined cooling, heating, and power (HPNE‐CCHP) system composed of a distributed generator and solar energy heat pump system. To obtain the optimum capacity of the HPNE‐CCHP system, nondominated sorting genetic algorithm‐II (NSGA‐II) was used to optimize the system by considering the life cycle cost (LCC) and life cycle pollutant emissions (LCPE) as the objective functions. A mixed integer economic scheduling model (MIESM) was proposed to make the HPNE‐CCHP system operate more economically. Finally, an HPNE‐CCHP system was constructed for a building in Northern China. The simulation results show that an HPNE‐CCHP system with a moderate proportion of new energy is more economical and environmentally friendly than a traditional CCHP system. Building occupants, depending on their desired spending, can select the best capacity configuration on the Pareto frontier. Although pollutant emissions will be reduced as the proportion of new energy increases, this type of configuration is expensive.